1997
DOI: 10.1016/s0025-6196(11)63567-2
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Intravenous Administration of Caffeine and Recovery After Ambulatory Surgical Procedures

Abstract: We conclude that prophylactic intravenous administration of caffeine was beneficial for those patients at risk for symptoms of caffeine withdrawal. For patients who consume caffeinated beverages on a daily basis, we recommend prophylactic administration of caffeine on the day of an ambulatory surgical procedure and anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…However, premorbid primary headache syndromes, even in otherwise solid papers (74), are seldom reported. It seems though that subjects with a history of frequent headaches (75) are at increased risk, and that migraineurs and subjects who experience withdrawal headache share some comorbidity such as major depression and anxiety (5). To “produce experimental headaches which would be more physiological than experimental histamine and nitrite headaches,” Dreisbach in 1940 gave a number of non-habitual coffee drinkers capsules of 10–12 grains (650–780 mg) of caffeine daily for 1 week and then withdrew the treatment.…”
Section: Resultsmentioning
confidence: 99%
“…However, premorbid primary headache syndromes, even in otherwise solid papers (74), are seldom reported. It seems though that subjects with a history of frequent headaches (75) are at increased risk, and that migraineurs and subjects who experience withdrawal headache share some comorbidity such as major depression and anxiety (5). To “produce experimental headaches which would be more physiological than experimental histamine and nitrite headaches,” Dreisbach in 1940 gave a number of non-habitual coffee drinkers capsules of 10–12 grains (650–780 mg) of caffeine daily for 1 week and then withdrew the treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the nonspecific adenosine receptor antagonist caffeine has been suggested for the prevention or treatment of postdural puncture headache 13. While this indication has been challenged, 13 caffeine remains an important therapeutic agent in the treatment or prevention of caffeine withdrawal headache in perioperative patients 14,15. Similarly, the non-specific adenosine receptor antagonist theophylline has been used in the past for treating obstructive airway disease, but has been replaced by inhaled long-acting beta-agonist bronchodilators due to less drug-drug interactions and toxicity from drug overdosing 16…”
Section: Introductionmentioning
confidence: 99%
“…There were 10 studies investigating the effect of caffeine peri-operatively and the development of post-operative headache [24][25][26][27][28][29][30][31][32][33] . Seven investigated caffeine withdrawal [24][25][26][27][28][29][30][31][32][33] and three studies administered oral caffeine to prevent post-operative headache [31][32][33] . Of the seven prospective studies investigating the effect of caffeine withdrawal, ve studies found caffeine withdrawal increased the incidence of post-operative headache [24][25][26][27][28][29][30][31][32][33] .…”
Section: Caffeine Use In the Peri-operative Periodmentioning
confidence: 99%